Visible light-driven photocatalytically active g-C3N4 material for enhanced generation of H2O2 - Zhu, Zedong; Pan, Honghui; Murugananthan, Muthu; Gong, Jianyu; Zhang, Yanrong (Applied catalysis. B, Environmental, 2018)
[Display omitted] •Reduced g-C3N4 was synthesized via direct heating with NaBH4.•Defects were successfully introduced into the reduced g-C3N4.•CN functional group narrowed the band gap and shifted down the VB energy level.•Nitride vacancies extended the spectral absorption.•Reduced g-C3N4 showed a high photocatalytic activity for the production of H2O2. Reduced g-C3N4 material was prepared by a thermal treatment of g-C3N4 in presence of NaBH4 under N2 atmosphere. The prepared catalyst material was characterized by using elemental analyzer, FTIR and XPS and the analysis showed that the reduction treatment created nitrogen vacancies followed by a formation of functional group CN owing to a break-up reaction in the pyridine nitride of a s-triazine-C3N4. The findings of UV–vis DRS and DFT calculation revealed that the formed functional group CN results in a narrowed energy band gap owing to positive shift in the conduction band as well as valence band. The downshift observed in the valence band level made the catalyst material with a feature of visible light-driven water oxidation capacity, that was confirmed by the electron and hole sacrifice and OH trapping-EPR techniques. The intermediate energy level within the band gap of g-C3N4 originated from the vacancies caused an extended absorption, especially to the visible region. The analysis of PL emission spectrum confirmed that the reduction treatment could facilitate the spatial separation of photo-excited electron and hole, and enhance the charge transfer as well. RDE studies showed that the selective production of H2O2 by two-electron reduction of O2 was a predominant reaction step using the reduced g-C3N4. The reduced g-C3N4 prepared at 370 °C exhibited an efficient visible light driven catalytic performance on H2O2 production (170 μmol/L h−1) from pure H2O and O2 at ambient atmosphere in the absence of organic electron donors. The solar-to-H2O2 chemical conversion efficiency and apparent quantum yield approached to ∼0.26%, ∼4.3%, respectively. In addition, the experimental results obtained on recycling of the prepared g-C3N4 evidenced the photocatalytic stability of the material.